Management of anemia in inflammatory bowel disease: a challenge in everyday clinical practice - Edyta Tulewicz-Marti; Andrzej Moniuszko; Grażyna Rydzewska (Gastroenterology Review)
Anemia is the most common extraintestinal manifestation and complication of inflammatory bowel disease (IBD). Its etiology is multifactorial and mostly is a combination of iron deficiency anemia (IDA) and chronic anemia (ACD). Because of its high incidence in patients with IBD and its influence on their quality of life, regular screening is recommended. In case of IDA type of medication and route of administration should be determined by many factors such as general condition of the patient, IBD activity or anemia severity. Intravenous iron supplementation is the preferred route but may be associated with phosphate drop or even severe hypophosphatemia (HP). The mechanism of HP related to the intravenous iron infusions is not clearly known yet, but it might be related to the change of FGF-23 levels. What more not all parenteral forms of iron are equal and some may have a higher risk of HP than others.